Impact of using humor advertisement on airline customers’ mental image - Tareq Hashem (Innovative Marketing)
The study aims to investigate the impact of using humor advertisements on airline customers’ mental image. To achieve the main objective, a questionnaire was designed according to research hypotheses. The study population consists of airline customers that operate in Jordan and those who were exposed to a humor advertisement on the planes. Each person was asked before filling the questionnaire if he was previously exposed during one of his flights to humor advertisement or not. A convenient sample of 700 people was selected, 587 valid questionnaires have been collected. The research concluded that humor advertising has a significant impact on the formation of airline customers’ mental image, moreover, aggressive humor variable is considered the most influential variable on airline customers’ mental image. The research suggested some recommendations, such as: airlines should adopt humorous marketing activities in high level, and to benefit from leading companies experiences in order to meet customer needs and desires. As well as, they should encourage customers to respond to them in expressing their opinion about humor advertisements they make.